Романістика В. Даниленка в контексті художніх шукань великої прози початку ХХІ ст. - Яблонська, Наталія Мирославівна; Yablonska, Natalia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті досліджено жанрові особливості романістики В. Даниленка в сучасному українському прозовому дискурсі, висвітлено форми авторської свідомості в його романах «Любов у стилі бароко», «Капелюх Сікорського», «Газелі бідного Ремзі» та ін., окреслено основні генологічні, стильові, наративні й образотвірні стратегії письменника. In the article the genre peculiarities of Danilenko’s romance are investigated in a modern Ukrainian prose discourse, the author’s consciousness forms are discussed in his novels «Love in the Baroque Style», «Sikorsky’s Hat», «Gazelles of Poor Ramsey» and others, the basic genealogic, stylistic, narrative and pictorial writer’s strategies are outlined. In particular, V. Danylenko cleverly simulates the genre of «polyphonic» novel mixing a detective, a historical novel, a gothic novel, the quest etc., creating ekfrasys novel («Love in the Baroque Style»), the original version of biographical novel («Sikorsky’s Hat»), grotesque satirical novel-mystification («Gazelles of Poor Ramsey»). He experimentally combines Baroque, Gothic, modernism, postmodernism poetics, structures the plot twists «on Baroque counterpoint principle», introduces a mystical or initiate discourse, which indicates myth-ritual scenario, provides art details with psychological loading.
Romance of V. Danilenko in the Context of the Artistic Pursuit of Large Prose at the Beginning of the XXI Century
Keywords: магічний реалізм; містифікація; постмодернізм; роман; сатира; жанр; genre; magic realism; mystification; postmodernism; novel; satire